Board Diversity and Environmental Disclosure Practices of Malaysian Public Listed Companies - Chong, Jennifer Lai Yee (Curtin University, 2018)
This thesis examines the influence of board diversity on the level of environmental disclosure of Malaysia listed companies from 2014 to 2016. Data is hand-collected from the published reports of companies from environmentally-sensitive industry sectors. Using stratified random sampling approach, 150 companies are selected for each period. Panel data analysis is employed. There is a statistically significant increase in environmental disclosure level. Younger and foreign directors are the negative predictors of the environmental disclosure.